2019
DOI: 10.2967/jnumed.118.222638
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of211At Uptake via the Sodium Iodide Symporter by the Addition of Ascorbic Acid in Targeted α-Therapy of Thyroid Cancer

Abstract: 211At is an α-emitter that has similar chemical properties to iodine and is used in targeted α-therapy. In the present study, we added ascorbic acid (AA) to 211At solution to increase the radiochemical purity of astatide and evaluated its efficacy against differentiated thyroid cancer, which is characterized by the expression of sodium/iodide symporter (NIS). Methods: Crude 211At solution (AA(−)) and 211At solution treated with AA (AA(+)) were prepared. Uptake by the thyroid was compared between the 2 solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 24 publications
4
82
0
1
Order By: Relevance
“…The estimated absorbed dose in the C6 glioma xenograft was 1.7 ± 0.6 Gy/MBq. In our previous study using 211 At-NaAt, the estimated dose was 9.7 ± 7.0 Gy/MBq in the K1-NIS xenograft, which showed better tumor retention [11]. Regarding the treatment effect, 211 At-NaAt treatment showed tumor Oncotarget 1392 www.oncotarget.com regression followed by the delayed regrowth, whereas 211 At-AtPA treatment showed tumor growth suppression in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The estimated absorbed dose in the C6 glioma xenograft was 1.7 ± 0.6 Gy/MBq. In our previous study using 211 At-NaAt, the estimated dose was 9.7 ± 7.0 Gy/MBq in the K1-NIS xenograft, which showed better tumor retention [11]. Regarding the treatment effect, 211 At-NaAt treatment showed tumor Oncotarget 1392 www.oncotarget.com regression followed by the delayed regrowth, whereas 211 At-AtPA treatment showed tumor growth suppression in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 95%
“…211 At-astatide is thought to be deastatinated during metabolic processes. We have previously reported the specific uptake of astatide in the thyroid gland through the sodium iodide symporter (NIS), in a manner similar to iodide, and identified the thyroid gland as an organ at risk [11]. We subsequently demonstrated that the thyroid uptake of 211 At-astatide, which was deastatinated from 211 At-PA, could be reduced by 80% following the pre-administration of iodine [22].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, we used 100 mL beakers and smaller 1.5 mL microtubes as vessels for 211 At aliquots to examine the vessel-size dependence of the dispersal rate of 211 At. Thin-layer chromatography (TLC), which is often used for chemical analysis of pharmaceuticals 8) and chemical studies 9) of At, was also performed to obtain information on formed chemicals species of 211 At. After bombardment, 211 At was separated from the irradiated Bi target 10) .…”
Section: Introductionmentioning
confidence: 99%